2015
DOI: 10.1016/j.virol.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of canine kobuvirus in wild carnivores and the domestic dog in Africa

Abstract: Knowledge of Kobuvirus (Family Picornaviridae) infection in carnivores is limited and has not been described in domestic or wild carnivores in Africa. To fill this gap in knowledge we used RT-PCR to screen fresh feces from several African carnivores. We detected kobuvirus RNA in samples from domestic dog, golden jackal, side-striped jackal and spotted hyena. Using next generation sequencing we obtained one complete Kobuvirus genome sequence from each of these species. Our phylogenetic analyses revealed canine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…Furthermore, the advent of next-generation sequencing has enabled the identification and characterization of several previously unknown viruses that can be transmitted between dogs and wildlife. These examples include canine kobuviruses (CaKoVs) [12][13][14][15], circoviruses [16,17], and sapoviruses [12,18]. Therefore, we hypothesized that the carnivore protoparvoviruses recently detected in dogs and cats [3,7] could also circulate among wild canids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the advent of next-generation sequencing has enabled the identification and characterization of several previously unknown viruses that can be transmitted between dogs and wildlife. These examples include canine kobuviruses (CaKoVs) [12][13][14][15], circoviruses [16,17], and sapoviruses [12,18]. Therefore, we hypothesized that the carnivore protoparvoviruses recently detected in dogs and cats [3,7] could also circulate among wild canids.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of CKoV in the USA, this virus has been identified in domestic dogs in Europe, Asia and South America ( Table 2). Isolates have also been identified in wild carnivores (foxes and jackals) in Europe and Africa (Di Martino et al, 2014b;Olarte-Castillo et al, 2015).…”
Section: Epidemiologymentioning
confidence: 99%
“…Canine kobuvirus (CaKoV) that was genetically related to human AiV was first identified in a domestic dog with acute gastroenteritis in USA in 2011 (Kapoor et al 2011), and was subsequently found in healthy domestic dogs (Oem et al 2014a) and wild carnivores, including wolves (Melegari et al 2018), red foxes (Di Martino et al 2014), golden jackals, side-striped jackal and spotted hyena (Olarte-Castillo et al 2015). To date, kobuviruses have been reported in human (Yamashita et al 1993), cattle (Yamashita et al 2003), sheep (Reuter et al 2010), pig (Reuter et al 2008), rodents (Phan et al 2011), goat (Oem et al 2014b), wild boars (Reuter et al 2013), roe deer (Di Martino et al 2015a), rabbits (Pankovics et al 2016), bats (Wu et al 2016), ferrets (Smits et al 2013), domestic and wild carnivores (Olarte-Castillo et al 2015) and cats (Chung et al 2013). According to the recent report of International Committee on Taxonomy of Viruses (ICTV) in 2017 (https://talk.ictvonline.org/taxonomy/), the genus Kobuvirus was classified into six officially recognized species, namely Aichivirus A (formerly Aichi virus), Aichivirus B (formerly bovine kobuvirus), Aichivirus C (porcine kobuvirus), Aichivirus D (kagovirus 1), Aichivirus E (rabbit kobuvirus) and Aichivirus F (bat kobuvirus), respectively (Adams et al 2013;Adams et al 2017).…”
Section: Introductionmentioning
confidence: 99%